2016
DOI: 10.7314/apjcp.2016.17.4.1705
|View full text |Cite
|
Sign up to set email alerts
|

Association of Viral Infections with Risk of Human Lymphomas, Egypt

Abstract: Background: The aim of this study was to determine and evaluate the association of different viral infections, with hepatitis B and C viruses, Epstein-Barr virus, cytomegalovirus and human herpes virus-8 (HBV, HCV, EBV, CMV, HHV-8) with the risk of lymphomas (Hodgkin and non-Hodgkin) among Egyptian patients, and correlate with the histopathological staging and typing as well as the prevalence of combined infections. Materials and Methods: A total of 100 newly diagnosed lymphoma patients with 100 healthy age an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
(25 reference statements)
1
4
1
1
Order By: Relevance
“…MZL was rare (7.5%). The distribution of NHL we report here is similar to previous findings in Egypt19,20,21 with DLBCL proportions of 55% to 76% among HCV associated NHL, MZL proportion being lower than 10% 21. Overall, our results are in agreement with many studies that reported HCV association with DLBCL, and MZL 6,10,24,25.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MZL was rare (7.5%). The distribution of NHL we report here is similar to previous findings in Egypt19,20,21 with DLBCL proportions of 55% to 76% among HCV associated NHL, MZL proportion being lower than 10% 21. Overall, our results are in agreement with many studies that reported HCV association with DLBCL, and MZL 6,10,24,25.…”
Section: Discussionsupporting
confidence: 92%
“…Confirming the role of HCV in lymphoma development, we report a strikingly high rate of HCV infection (61%) among patients with NHL in the Mansoura region, which appears to be the highest reported to our knowledge in the literature. Previous studies on the malignant complications of chronic HCV infection in Egypt or focusing specifically on the association between HCV and NHL reported an HCV prevalence ranging from 40 to 50% among patients with NHL 19,20,21,23. The higher rate we report in the Delta region may be explained by the higher prevalence of HCV in this region.…”
Section: Discussioncontrasting
confidence: 49%
“…The HBsAg seropositive patients showed an elevated risk, for the most part, of B-NHL and a few subtypes of T-NHL, particularly in DLBCL, which was consistent with Taborelli’s report. [8] Conversely, a non-significant association between HBsAg positivity and NHL was found in Kadry’s study [28]. Notably, the HBsAg seropositive patients had 2.13 times greater odds of being diagnosed with SLL/CLL than the controls, which was inconsistent with most previous studies [8, 9, 21, 22, 26, 29, 36, 43].…”
Section: Discussionmentioning
confidence: 73%
“…They did not find any significant difference in IHC subclasses and clinical data between EBV-positive DLBCL of young and old groups. Kadry et al [ 12 ] compared 100 newly diagnosed Egyptian lymphoma patients with 100 healthy age- and sex-matched normal controls for the presence of hepatitis B and C (HBV, HCV) viruses, EBV, cytomegalovirus (CMV), and human herpes virus-8 (HHV-8). There was high indication of presence of most viruses in lymphoma cases except for positive HBs Ag, positive CMV IgG, and HHV-8.…”
Section: Viruses and Lymphomamentioning
confidence: 99%